The derivative of the value of parametric antagonistic game - Budreika, B.; Vilkas, E. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Б. И. Будрейка, Э. И. Вилкас. Производная значения параметрической антагонистической игрыB. Budreika, E. Vilkas. Parametrinio antagonistinio lošimo reikšmės išvestinė